2005
DOI: 10.1038/nature03812
|View full text |Cite
|
Sign up to set email alerts
|

The Lyme disease agent exploits a tick protein to infect the mammalian host

Abstract: The Lyme disease agent, Borrelia burgdorferi, is maintained in a tick-mouse cycle. Here we show that B. burgdorferi usurps a tick salivary protein, Salp15 (ref. 3), to facilitate the infection of mice. The level of salp15 expression was selectively enhanced by the presence of B. burgdorferi in Ixodes scapularis, first indicating that spirochaetes might use Salp15 during transmission. Salp15 was then shown to adhere to the spirochaete, both in vitro and in vivo, and specifically interacted with B. burgdorferi o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
422
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(431 citation statements)
references
References 30 publications
5
422
1
3
Order By: Relevance
“…Despite the rapid feeding of mosquitoes, mosquito saliva clearly has immunomodulatory activity, and mounting data demonstrate that, as a consequence of this activity, mosquito-borne pathogens may be delivered to the vertebrate in an environment that is compromised in its ability to respond to and contain infection. As with other pathogens that have visibly co-evolved with the vector to take advantage of arthropod saliva and the unique immune environment it creates (Ramamoorthi et al 2005), arboviruses also appear to exploit this niche to improve transmission and survival. Continuing research into the effect of mosquito saliva on host immune response and arbovirus infection will not only provide a progressively more accurate understanding of mosquito-transmitted virus pathogenesis, but may uncover the means to disrupt transmission or diminish disease by, in conjunction with viral prophylactic strategies, undermining the action of salivary proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the rapid feeding of mosquitoes, mosquito saliva clearly has immunomodulatory activity, and mounting data demonstrate that, as a consequence of this activity, mosquito-borne pathogens may be delivered to the vertebrate in an environment that is compromised in its ability to respond to and contain infection. As with other pathogens that have visibly co-evolved with the vector to take advantage of arthropod saliva and the unique immune environment it creates (Ramamoorthi et al 2005), arboviruses also appear to exploit this niche to improve transmission and survival. Continuing research into the effect of mosquito saliva on host immune response and arbovirus infection will not only provide a progressively more accurate understanding of mosquito-transmitted virus pathogenesis, but may uncover the means to disrupt transmission or diminish disease by, in conjunction with viral prophylactic strategies, undermining the action of salivary proteins.…”
Section: Resultsmentioning
confidence: 99%
“…A recent genetic study showed that the midgut protein TROSPA is a receptor for OspA binding, whose presence enhances colonization by B. burgdorferi [170]. The salivary gland protein Salp15 is immunosuppressive and may facilitate infection by the low numbers of spirochetes that are transmitted during tick feeding [171,172]. Recently, a tick antioxidant was shown to facilitate tick acquisition of spirochetes from infected animals [173].…”
Section: B Burgdorferi Infection Of Ticksmentioning
confidence: 99%
“…The function of this protein was unknown for a long time. Recently the ligand for OspC -tick salivary immunosuppressive protein Salp15 -was described 109 . It is a soluble component of tick saliva which suppresses the vertebrate host immune response against components of tick saliva during tick engorgement.…”
Section: Outer Surface Protein Cmentioning
confidence: 99%